Occupational motions such as kneeling and squatting are associated with the increased development of medial meniscus posterior root tears, regardless of the medial posterior tibial slope angle - Koki Kawada; Yusuke Yokoyama; Masanori Tamura; Yuki Okazaki; Toshifumi Ozaki; Takayuki Furumatsu (Journal of Experimental Orthopaedics)
Abstract Purpose The relationship between occupational motions and the medial posterior tibial slope (MPTS) with the development of medial meniscus posterior root tears (MMPRTs) has not been investigated. The development of non‐traumatic degenerative MMPRTs may be influenced by repetitive occupational motions and bone morphological characteristics. Herein, we examined the association between occupational motions and MPTS in patients with MMPRT development. Methods During the first medical examination, MPTS was measured using lateral knee radiographic images, and occupational motions were investigated in 559 patients (591 knees). Occupational motions were classified as kneeling and squatting, standing and walking, sitting, lifting heavy weights, and housework. Mann–Whitney U test was used to compare patient characteristics between male and female patients and MPTS relative to occupational motion. Results The most frequent occupational motion was housework (160/559 patients, 28.6%), followed by kneeling and squatting (140/559, 25.0%), standing and walking (128/559, 22.9%), sitting (82/559, 14.7%), and lifting heavy weights (49/559, 8.8%). Furthermore, housework (10.0 ± 2.6°) involved significantly greater MPTS than kneeling and squatting (9.3 ± 2.7°; p = 0.012). However, the MPTS associated with other occupational motions was not significantly different from that associated with housework. Conclusion The most frequent occupational motion among patients with MMPRTs was housework, followed by kneeling and squatting. Patients who performed housework tended to have a higher MPTS. Occupational motions such as kneeling and squatting potentially increase the development of MMPRTs, even without a high MPTS. Level of Evidence Level IV.